2016
DOI: 10.1080/02626667.2015.1085991
|View full text |Cite
|
Sign up to set email alerts
|

Pre-processing of data-driven river flow forecasting models by singular value decomposition (SVD) technique

Abstract: An appropriate streamflow forecasting method is a prerequisite for implementation of efficient water resources management in the water-limited, arid regions that occupy much of Iran. In the current research, monthly streamflow forecasting was combined with three data-driven methods based on large input datasets involving 11 precipitation stations, a natural streamflow, and four climate indices through a long period. The major challenges of rainfallrunoff modelling are generally attributed to complex interactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…These studies were able to provide the estimated climate signals. Bretherton et al [31] compared four different techniques (PCA, CCA, SVD, and single-field PCA) and Chitsaz et al [52] compared SVD with PCA, and both concluded that SVD was the easiest method to implement and superior to the other methods. It is easy to implement as it untangles data into independent components that are easy to analyze.…”
Section: Statistical Approachmentioning
confidence: 99%
“…These studies were able to provide the estimated climate signals. Bretherton et al [31] compared four different techniques (PCA, CCA, SVD, and single-field PCA) and Chitsaz et al [52] compared SVD with PCA, and both concluded that SVD was the easiest method to implement and superior to the other methods. It is easy to implement as it untangles data into independent components that are easy to analyze.…”
Section: Statistical Approachmentioning
confidence: 99%
“…Additionally, it is characterized by its low computational complexity ( 62 , 63 ). It is also worth mentioning that singular value decomposition demonstrated superior dimensionality reduction accuracy against principal component analysis according to a set of performance evaluation tests ( 64 , 65 ).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Thus, AI modeling has been widely used for streamflow forecasting in recent years because of the availability of long-term gauging data, the ever-increasing computational power. For example, Chitsaz et al [4] proposed a pre-processing based model to forecast monthly streamflow. They considered three data-driven models, generalized regression neural network (GRNN), multi-layer perceptron (MLP), and adaptive neuro fuzzy inference system (ANFIS) and pre-processing techniques, such as principal component analysis (PCA), singular value decomposition (SVD) and average values of inputs for their aims.…”
Section: Introductionmentioning
confidence: 99%